Genetic polymorphism of prolactin and nitric oxide synthase in Holstein cattle - Indira Saltanovna Beishova; Alena Valentinovna Belaya; Yusupzhan Artykovich Yuldashbayev; Gulzhagan Dzhambulovna Chuzhebayeva; Vadim Alexandrovich Ulyanov; Tatyana Vladimirovna Ulyanova; Alexandr Mikhailovich Kovalchuk; Ulbolsyn Zhangaziyevna Kuzhebayeva; Aidar Myrzahmetuly Namet (Veterinary World, 2023)
Background and Aim: Bacterial and viral infections affect the welfare of animals and lead to large economic losses in dairy cattle breeding due to decreased productive indicators and increased culling rates. In modern dairy farming, farmers are looking for effective solutions to prevent and minimize infectious disease risks. To this end, the most relevant study field is the search for gene sites that impact production and health. This study aimed to determine the nature of the distribution of the relative frequencies of alleles and genotypes of polymorphic prolactin (PRL) and nitric oxide synthase (NOS2) in Holstein cows and identify the relationship of these genes with resistance to mastitis and bovine leukemia.